Validation of the Spanish Language Version of the Learning and Performance Orientations in Physical Education Classes Questionnaire. (Validación de la versión Española del Cuestionario de Orientaciones al Aprendizaje y el Rendimiento en las clases de Educación Física). - Eduardo M. Cervelló Gimeno; Ruth Jiménez Castuera; Manuel Moya Ramón; Juan Antonio Moreno Murcia (Ramón Cantó Alcaraz, 2010)
Abstract The objective of this study was to examine the factorial validity and reliability of the Learning and Performance Orientations in Physical Education Classes Questionnaire (LAPOPECQ) with adolescent Spanish physical education students. Exploratory and confirmatory factor analysis were utilized to address this question. Results of the exploratory factor analysis revealed the presence of five factors and was consistent with previous research. Confirmatory factor analysis indicated that the Spanish version of the LAPOPECQ had fit indices that were similar to the original Greek and English versions of the instruments and that a five-factor correlated model was more parsimonious than a hierarchical model. The implications of these findings on future research are discussed. Resumen El objetivo de este estudio fue examinar la validez de constructo y fiabilidad del Cuestionario de orientaciones al aprendizaje y al rendimiento en las clases de Educación Física (LAPOPECQ) en adolescentes españoles estudiantes de educación física. Fueron empleados análisis factoriales exploratorios y confirmatorios para abordar esta cuestión. Los resultados del análisis factorial exploratorio revelaron la presencia de cinco factores. Esta estructura era coherente con la investigación anterior. El análisis factorial confirmatorio indicó que la versión en español del LAPOPECQ presentaba índices de ajuste similares a las versiones en griego e inglés del test. El modelo de cinco factores correlacionados fue más parsimonioso que un modelo jerárquico. Se discuten las implicaciones de estos hallazgos en la investigación futura.